Profesionalisme Hakim Pengadilan Agama Dalam Memutuskan Perkara Pendekatan Ushuliyyin Dalam Masalah Warisan - Hafidzi, Anwar (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2019)
This study aims to find a legal pattern for the distribution of inheritance in the Banjarmasin community which was submitted through the Banjarmasin Religious Court Judge. the problem to be achieved is how the ability of judges to decide cases about inheritance in 2016-2017. This research is literature with the document data on decisions about inheritance analyzed through a juridical-normative approach and processed through descriptive analytic normative-qualitative followed by a usul approach to the results of the distribution of inheritance. This correlation will result in the professionalism of judges from aspects of understanding, mastery, and juridical skills. The results of the study found that the ability of judges in understanding decisions was very good in examining the problems of determining the heirs proposed. The judge's proficiency in using Laws and KHI about inheritance is also in accordance with the results obtained. The ushul approach found that the concept of Radd from jurisprudence is given to furudh dzil except husband and wife, while KHI is for all heirs. Likewise, joint property disputes, it was found that the concept of al-‘urf is part of juridical considerations. Keywords: Professionalism, judge, inheritance, usul